Efficiency of an integrated habitat stabilisation approach to coastal erosion management - Kamali, B.; Hashim, Roslan; Akib, S. (Academic Journals, 2010)
The present paper describes the technical solution adopted for habitat stabilisation as an integrated approach to erosion mitigation aimed at improving ecological and environmental aspects of the tropical and subtropical shorelines. Any man-made structure on the beach could have an environmental impact on the habitat and the associated biota. However, when the habitat is considered in the design process, a coastal erosion management plan can provide an effective means of coastline stabilisation and habitat enhancement. Therefore, in this study a combination of low crested breakwaters and a mangrove restoration plan was applied to an intertidal beach on the west coast of the state of Selangor, Malaysia. The study was aimed at protecting the beach and enhancing the habitat. The presence of the breakwater resulted in sediment deposition on the beach and the substrate elevation increased to a height appropriate for mangrove establishment. The calm area protected by the breakwater was also conducive to restoration work on the exposed coast. The approach provided suitable conditions for coastal rehabilitation, facilitating the natural recovery process of the coastal ecosystem.